Evolution of Yeast Consortia during the Fermentation of Kalamata Natural Black Olives upon Two Initial Acidification Treatments - Bonatsou, Stamatoula; Paramithiotis, Spiros; Panagou, Efstathios Z. (Frontiers in Microbiology, 2018)
The objective of this study was to elucidate the yeast consortia structure and dynamics during Greek-style processing of Kalamata natural black olives in different brine solutions. Olives were subjected to spontaneous fermentation in 7% (w/v) NaCl brine solution (control treatment) or brine acidified with (a) 0.5% (v/v) vinegar, and (b) 0.1% (v/v) lactic acid at the onset of fermentation. Changes in microbial counts (lactic acid bacteria-LAB, yeasts, Enterobacteriaceae), pH, acidity, organic acids (lactic, acetic, citric, malic, tartaric, succinic), sugars (glucose, fructose), and alcohols (ethanol, glycerol) were analyzed for a period of 187 days. Yeast consortia diversity was evaluated at days 4, 34, 90, 140, and 187 of fermentation. A total of 271 isolates were characterized at sub-species level by rep-PCR genomic fingerprinting with the oligo-nucleotide primer (GTG)5. The characterization of yeast isolates at species level was performed by sequencing of the D1⁄D2 domain of 26S rRNA gene. Results showed that yeasts dominated the process presenting a relatively broad range of biodiversity composed of 12 genera and 21 species. No LAB or Enterobacteriaceae could be enumerated after 20 and 10 days of fermentation, respectively. The dominant yeast species at the beginning were Aureobasidium pullulans for control and vinegar acidification treatments, and Candida naeodendra for lactic acid treatment. Between 34 and 140 days the dominant species were Candida boidinii, Candida molendinolei and Saccharomyces cerevisiae. In the end of fermentation the dominant species in all processes were Candida boidinii and Candida molendinolei, followed by Pichia manshurica and S. cerevisiae in lactic acid acidification treatment, Pichia manshurica in vinegar acidification treatment, and Pichia membranifaciens in control fermentation.